Processing tomato chlorophyll a/b-binding protein 1C interacts with CMV 2b protein. (July 2022) - Liu, Zhen; Yu, Chengmin; Xiang, Benchun; Niu, Jianxin; Zheng, Yinying
Abstract: Light-harvesting chlorophyll a /b-binding proteins (LHCs) are nuclear-encoded thylakoid membrane proteins. In tomatoes, the Cab-1C gene encodes the type I Lhcb1 protein in LHCII. The GAL4 yeast two-hybrid system and BiFC experiments showed an interaction between SlCab-1C of processing tomato and the CMV 2b protein. At 56 dpi, the accumulation of CMV CP in the apical leaves of transgenic tobacco overexpressing the processing tomato Cab-1C gene was significantly reduced compared to wild-type tobacco. In addition, the interaction region between CMV 2b and SlCab-1C was located at amino acids 43–184 of the SlCab-1C protein. Highlights: SlCab-1C and CMV 2b interact in plants. The overexpression of SlCab-1C affects CMV CP accumulation in tobacco leaves. The region where SlCab-1C interacts with CMV 2b is located at amino acids 43–184 of the SlCab-1C protein.